Mechanistic Aspects of Inflammation and Oxidative Stress and Their Association With Thyroid Cancer Risk - Bo‐Tao Zhang; Mao Guo; Liu‐Rui Yang; Yang Zeng; Jun Jiang (Cancer Medicine)
ABSTRACT Aim To investigate the mechanistic aspects of inflammation and oxidative stress and their association with thyroid cancer risk. Methods We have systematically searched the PubMed and Web of Science databases to perform a comprehensive analysis of the pathogenic mechanisms that link obesity, inflammation, and oxidative stress to thyroid cancer. Results Chronic inflammation, a well‐known risk factor for cancer progression, is a hallmark characteristic of obesity. Multiple mechanisms may mediate the association between thyroid cancer and obesity. As a crucial endocrine organ, adipose tissue regulates tumor behavior, inflammation, and the tumor microenvironment through adipokines, including leptin, adiponectin, as well as chemokines. Excessive fat accumulation leads to an increase in pro‐inflammatory factors, which in turn result in systemic inflammation that can further influence tumor growth and development. Oxidative stress, characterized by an imbalance between the production of reactive oxygen species (ROS) and their elimination by antioxidants, can potentially result in cellular damage and destruction. With the accumulation of ROS, it participates in numerous diseases, such as cancer and inflammation. The inflammatory condition of the thyroid gland serves as a classical source of ROS, which may, in turn, promote the development of thyroid tumors. Conclusion While various mechanisms may elucidate the relationship between inflammation, oxidative stress, and the risk of thyroid cancer, the interplay among these factors is intricate and cannot be solely attributed to a singular pathway. This review provides further insight into a strategy for the prevention and treatment of thyroid cancer, highlighting the significance of combinatorial approaches that target multiple pathways in antitumor therapy.